Climate refugees or climate migrants: How environment challenges the international migration law and policies - Marina Andeva; Vasilka Salevska-Trajkova (University American College Skopje, 2020)
Climate change is causing millions of people to migrate from their homelands. Climate impacts that unravel over time, such as desert expansion and sea level rise, are forcing people from their homes: A World Bank report projects that within three of the most vulnerable regions - sub-Saharan Africa, South Asia and Latin America - 143 million people could be displaced by these impacts by 2050 (World Bank, 2018). A study by Columbia University climate researchers in the peer-reviewed journal Science projected that if global temperatures continue their upward march, applications for asylum to the European Union could increase 28 percent to nearly 450,000 per year by 2100 (Missirian and Schlenke, 2017). The International Organization for Migration in the past decade focused on bringing climatic and environmental factors to the light and on building a body of evidence proving that climate change affects - directly and indirectly - human mobility. Nevertheless, climate migrants have been invisible for many years on the migration and climate debates concerning their legal status and regulation. This paper will focus primarily on analysis of these phenomena with a specific focus on the terminology used and the interpretations of the existing legal instruments. Furthermore, it put emphasis on case-law analysis in terms of preparedness of national governments to confront this new category of migrants. In order to do so, this paper presents a specific case in front of the UN Human Rights Committee, Ioane Teitota vs. New Zealand, and discusses the impact of this case over the definition of "climate refugees," who currently lack any formal definition, recognition or protection under international law. The paper also underlines several recommendations to address this phenomena.
Keywords: 330; climate change; natural disasters; climate refugees; asylum; forced migration